Exploring the effects of strategic intervention in fostering autonomy in learning grammar - Pawlak, Mirosław; Kruk, Mariusz (Glottodidactica, 2025)
The present paper reports the findings of a quasi-experimental study which investigated the effects of strategy-based instruction targeting grammar learning strategies (GLS) on the development of autonomy in learning English grammar. Participants were 55 Polish university students, English majors in the first year of a three-year BA program, divided into an intervention group (43 students) and a control group (12 students). The intervention focused on different types of GLS and was implemented in eight 30-minute segments during regularly scheduled classes over one academic semester. The data were collected on the pretest, posttest and delayed posttest by means of the Grammar Learning Autonomy Scale (GLAS), a research instrument specifically created for the purpose of the study. Analysis of variance failed to show statistically significant differences within and between the two groups, indicating that the intervention failed to impact autonomy in learning grammar among the participants. Item-level analysis provided evidence for a positive effect of the treatment with respect to the belief that progress in learning L2 grammar depends on the teacher. Limitations of the study are presented and directions for future research are outlined.